Implementasi Putusan Hakim Dalam Menjatuhkan Putusan Tindak Pidana Penipuan Yang Dilakukan Anak Dibawah Umur: Studi Perkara Nomor 2/Pid.Sus-Anak/2022/PN.Tjk - Endang Prasetyawati; Indah Satria; Yosi Oktavia (Jurnal Hukum Sasana, 2022)
The problem of crime acts never seems to disappear and is never completely resolved. This also has an impact on the increasing number of criminals among minors. At present, it is suspected that the number of underage children involved in criminal acts is increasing. This is related to the pattern of daily life of children and social pressures. The objectives to be achieved in this research are to find out, understand, and analyze the efforts of the child protection commission in providing legal protection for minors who commit criminal acts and to analyze the basis for judges' considerations in deciding cases of criminal acts of fraud committed by minors. The use of this research is also expected to add theoretical, practical, and analytical references as a way out in criminal law. The research method used is empirical juridical research. Legal protection for children can be interpreted as an effort to protect the law against various freedoms and children's human rights and various interests related to children's welfare. Child protection can be done directly or indirectly. Directly, meaning that the activities are directly aimed at children who are the target of direct treatment. Activities like this can be in the form of protecting children from various threats from outside and within themselves. The judge's decision is very decisive in a case at trial, because in the judge's decision it determines the fate of a person being detained or not, of course in making a decision the judge must really consider everything that is presented before the court, because not only the fate of the accused is determined by the judge's decision but also the fate of a defendant's family. The Bapas and Kpai are also very decisive in the decision because the advice from the Bapas and the Kpai is also one of the basic considerations for the judge in making a decision, the Bapas and the Kpai must also accompany the child from arrest to the decision in accordance with the governing law.